Factors Affecting Cognitive Function in Elderly - Prihanti, Gita Sekar; Wilyani, Dwi; Hanif, Achmad; Azizah, Afaf; Lilo, Atika Rachmania; Imaniah, Humairoh Nur Permata; Fadhila, Nadia Farah; Nastiti, Tiara Andini Putri; Purnama, Wahyu Dwi (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background: The number of cognitive impairments in elderly increases gradually every year. The increasing number of elderly can bring various impacts. It has a positive impact if the elderly are in good health. It becomes a negative impact if the elderly have health problems. Mini-Mental Status Examination (MMSE) is a standard and simple test to evaluate cognitive function in elderly.Objective: To determine factors affecting cognitive function in elderly at Bandar Lor Sub-District, Sukorame Public Health Center, Kediri.Methods: This study used an analytical observational study with a cross-sectional design. The sample is 448, using simple random sampling technique. Respondents filled out MMSE questionnaire. Bivariate data analysis used chi-square test. Multivariate data analysis used a logistic regression test.Results: Factors affecting cognitive function in elderly are age, education, living together, history of illness, social activity, depression, MNA, work, physical activity, and marital status. Meanwhile gender, insomnia, and smoking have no effect. Multivariate test results found 3 factors that most affects cognitive function are depression (p = 0,000; OR 2,773; CI95% 1,643-4,680), MNA (p = 0.006; OR 1,928; CI95% 1,209-3,706), physical activity (p = 0.001; OR 0.926; CI95% 0.144-0.609).Conclusion: Family relationships and social support are essential to improve cognitive function.